Otorhinolaryngologic manifestations of cystic fibrosis: literature review - Carvalho, Carolina Pimenta; Teixeira, Daniel Caldeira; Ribeiro, Carolina Gonçalves; Barreiros, Aureliano Carneiro; Fonseca, Marconi Teixeira (International Archives of Otorhinolaryngology, 2008)
Introduction: Cystic Fibrosis is the most common recessive autosomic genetic disease among Caucasians. It's caused by mutations in the gene that decodes regulatory protein for transmembrane conductance, resulting in defective transport of chlorine. Objective: Review the literature about Cystic Fibrosis, with emphasis on otorhinolaryngologic manifestations. Method: The online Pub Med databases were researched and we applied the following search terms Fibrosis Cystic and Sinusitis, and Mucoviscidosis and Sinusitis. Conclusions: Although it is not the main cause of death, the otorhinolaryngologic manifestations of the Cystic Fibrosis bring important morbidity to these patients.